External Beam Radiotherapy ± Chemotherapy in the Treatment of Anal Canal Cancer: A Single-Institute Long-Term Experience on 100 Patients. (3rd July 2014) - De Bari, Berardino; Buglione, Michela; Maddalo, Marta; Lestrade, Laëtitia; Spiazzi, Luigi; Vitali, Paola; Barbera, Fernando; Magrini, Stefano M.
Abstract : One-hundred patients treated with curative radiotherapy (RT) ± chemotherapy (CT) for an anal canal carcinoma (T1–4N0–3M0) were retrospectively analyzed. Five- and 10-year local control (LC) rates were 73% and 67%, respectively. Acute and late G3–G4 toxicity rates were 32% and 12%, respectively. Two patients underwent a colostomy for a G4 anal toxicity. This study confirms the outcomes of RT ± CT in the treatment of anal canal cancer. Concomitant CT and LC statistically influenced Overall Survival and Colostomy-Free Survival. CT also statistically reduced the risk of nodal relapse. High rates of acute skin toxicity impose tailored volumes and techniques of irradiation.